A formação da liberdade religiosa: peculiaridades e vicissitudes no Brasil - Nara Pereira Carvalho (2011)
Religiousness is one the elements that can be considered by the human person for the achievement of a happy life. In a democratic and secular context, in which plurality must be acknowledged and the respect for individual choices be a prime concern, on the matter of religiousness there is the personality right religious liberty that consists, sucinctly, in having, not having or being able to change religious affiliation, as well as manifesting religious convictions in the private and public sphere. Since the religiousness can be embraced as a constitutive element of the human person, whose relations are local and global, religious liberty effectiveness should be sought beyond the borders of the Nation-Estate. For such, education has precipuous role. In Brazil, specifically, religious liberty was first formally guaranteed in 1890. This notwithstanding, this right has had a precarious development in the country. There are several attempts of incursions from religions in the public sphere, including in Law. Simultaneously, and despite the diversity, the choice for atheism is rejected by a large part of the population. Under the perspective of secularization, it is noticeable the dicey status of a plural and democratic environment, and, under the perspective of religious liberty, that it is necessary to increment personal autonomy so that persons can truly choose their values, including those associated with religiousness